PENGARUH METODE LATIHAN KEKUATAN LENGAN TERHADAP AKURASI PASSING ATAS DALAM PERMAINAN BOLA VOLI - Aldi Budiana (STKIP Muhammadiyah Kuningan, 2023)
Aldi Budiana, with the title “Arm Strength Training Method for Upper Passing Accuracy in Volleyball”. This overhead passing technique is easy when seen but difficult when doing it because when doing this top pass it must require strong arm strength and good accuracy/accuracy to reach the intended target so that this top passing can be done well and right when playing volleyball. The research aims to determine the effect of arm strength training on the accuracy of passing over the extracurricular students of MTS Negeri 7 Kuningan in volleyball games. This study uses an experimental research method with a one-group pretest-posttest research design. The results of this study using the SPSS 21 program with a significant level of 0.05, it was found that the average pretest score was 16.29 and the posttest average was 20.06. Based on the results of this study, it can be concluded that the push-up and handgrip training model can be developed and applied in the process of practicing over-passing accuracy in volleyball. Keyword : Accuracy, practice model, passing over